Development of a Rental Vehicle Tax Monitoring System Using the RAD Method and Automated Reminder Notifications - Yulia Hapsari; Wiranty; Desi Apriyanty; Alem Pameli (Universitas Mohammad Husni Thamrin, 2026)
Efficient management of vehicle tax obligations is essential for rental companies to ensure operational continuity and regulatory compliance. However, PT Go Rental still relies on manual procedures for recording tax information and reminding users of upcoming tax due dates. This practice increases the risk of delayed tax payments, difficulties in monitoring vehicle tax status, and potential administrative sanctions. To overcome the identified challenges, this research focuses on developing a web-based vehicle tax monitoring system designed to support a more streamlined and integrated tax management process. The system was built using the Rapid Application Development (RAD) approach, which promotes iterative system development and continuous user participation throughout the stages of requirements analysis, system design, implementation, and evaluation. The application was developed using PHP with the Laravel framework, while MySQL was employed for data storage and management. The functionality of the proposed system was assessed through black-box testing to ensure that each module operated in accordance with the defined specifications. The resulting application offers various features, including vehicle tax tracking, vehicle information management, tax payment reporting, and automated reminder notifications for upcoming tax due dates. The testing process confirmed that all system components functioned as intended and effectively assisted users in managing vehicle tax information. Furthermore, the implementation of the system is expected to minimize delayed tax payments, enhance administrative performance, and improve the availability of monitoring information for organizational decision-making.